Analisa Pengaruh Kepuasan Kerja Dosen Tetap Program Studi Kebidanan Semarang Tahun 2005 - Sujianto, Untung (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background : A changing of Nursing Education Institution into Midwifery Education Institution has made a major impact due to lecturers. Its impact is on both internal and external aspect which caused incomplete learning-teaching process, non maximum attendance of lecturers and decreasing activities of lecturers On the past three years thereâ€™s been a decreasing number in graduation and interests. The research aims is to identify and analyze factors which influencing the perception of the task satisfaction of lecturers on Midwifery Study Program of Health Politechnic SemarangMethod: The study is an explanatory research with a survey research method using a cross sectional approach. The research samples are all of lecturers in Midwifery Study Program of Health Politechnic Semarang on November 2005 (34 persons). Data were gathered through questioner (quantitative), analyzing in univariate, bivariate and multivariate. A indepth interview (qualitative) were also conducted on 3 responders.Result: The result of the research showing an influence between rank, amount of training followed and the sum of subject taught to a task satisfaction of lecturers stays well on work, head office, colleague, promotion nor compensation. Meanwhile rank and education do notinfluence task satisfaction of lecturers stays well on work, head office colleague, promotion nor compensation. A freeâ€ variables that become a predictor of task satisfaction in work are sum of training and subjects taught, a working satisfaction of head office is training, a satisfaction of colleague are sum of training, a satisfaction of promotion is education and a satisfactory of compensation is education. The most significant factors that influence a working satisfactory Is sum of training followed. In general responder satisfaction is lower (71%). A task satisfaction consists of satisfaction due to compensation lower (71%), a satisfaction due to head office lower (67.7%), a satisfaction due to task lower (67.7%), aÂ satisfaction due to colleague lower (61.3%) and satisfactory of promotion higher (54:8%)Keyword: Task satisfaction, Lecturer, Midwifery, Training